Normalizing masochism: subversion and reification of hegemony in Larry Kramer's The Normal Heart - Tay, Lai Kit; Sedehi, Kamelia Talebian (Universiti Putra Malaysia Press, 2016)
In its broadest sense, hegemony is defined as a set of agreed ideologies practiced by prominent regimes and governments which influences people’s minds. One of the practices which can be observed in most societies is the exclusion and rejection of homosexuals of their fundamental rights as humans. As such, the issue will be magnified in this paper through a satirical play written by Larry Kramer, entitled The Normal Heart. Parallel with the dominant hegemony, the homosexual characters in the play are mistreated and isolated within their own society. To retaliate, these characters consider themselves as victims and intend to counter the situation by masochism. However, the attempt seems to backfire and reify the preexisting hegemony. As such, this paper explores The Normal Heart in light of Antonio Gramsci’s concept of hegemony as well as Erich Fromm’s masochism. To further specify, the paper examines the homosexual characters – their victimization and their fight against the dominant ideologies and how it all leads to their estrangement within the society.